The TeX Live guide, version 2 - Rahtz, S; Goossens, M (TeX Users' Group, 1997)
This documentation describes the main features of the TEX Live CD-ROM, a TE X/LATEX distribution for Unix, Windows32, Amiga and NeXT systems, that includes TEX, LATEX2e, METAFONT, MetaPost, many other programs such as Makeindex, dvips, xdvi and BIBTEX; and a very complete set of macros, fonts and documentation conforming to the TEX Directory Standard which can be used with nearly every TEX setup. This TEX package uses theWeb2c implementation of the programs, which tries to make TEXing as easy as possible, and takes full advantage of the efficient and highly customizable Kpathsea library from Karl Berry. It can be run either directly from the CD-ROM, or installed on a hard disk.